A Case Study of Milk Processing Plant of Parag Dairy Faizabad - Gautam, Rakesh B.; Maurya, Raj Mani; Ram, Ramjeet Singh Sangam; Verma, Satish kumar; Agrahari, Sandeep; Kumar, Sudheer; Maurya, Sri Prakash; Verma, Atul Kumar (International Journal of Bio-resource and Stress Management, 2018)
India is endowed with a largest livestock population in the world having a total bovine population of 304 million compared to the world total bovine population of 1400 million. There has been a major improvement in milk production, which increased from 17 mt in 1951 to 127.9 mt during 2011–12. Per capita availability of the milk has reached a level of 290 g day-1 during the year 2011–12, which more than the world average of 284 g day-1. Most of the milk in the country is produced by small, marginal farmers and landless laborers. In order to increase milk production, the government has approved national dairy plan phase-1 (NDP-1) in February, 2012 with a total investment of about Rs. 2242 core to be implemented from 2011–12 to 2016–17. Department of animal husbandry, dairying and fisheries, ministry of agricultural Government of India is also implementing “national program on bovine breeding and dairy development (NPBBDD) from 2013–14 to 2016–17 through the state implementing agencies/end implementing agencies/participating agencies. The organized dairy sector (both cooperative and private) is presently handling about 15% of the total milk production in the country. Dairy products form one of the fastest growing segments in livestock product export. India’s export of dairy product was 25928.52 mt to the world for the worth of Rs. 4318.53 cores during the year 2015–16.